2016
DOI: 10.1108/ijshe-05-2015-0098
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development in Vietnam: lessons learned from teacher education

Abstract: Purpose The purpose of this paper is to identify challenges in education for sustainable development (ESD) implementation in teacher education institutions (TEIs) in Vietnam and propose some appropriate solutions to advance ESD in training teachers toward sustainability. Design/methodology/approach The authors interviewed ten lecturers and 75 students in five TEIs across Vietnam and organized focus groups to obtain qualitative data which were coded to identify themes and provide quantitative results for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 24 publications
2
50
0
5
Order By: Relevance
“…The main factors hampering implementation were teaching methodology and teachers' capacity. For instance, the research of Kieu et al [31] revealed that teaching methods were one of the main reasons for student negative feedback toward ESD at the university level. Students claimed the courses were boring due to the lack of interactive teaching and learning, excessive content and poor facilities.…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
“…The main factors hampering implementation were teaching methodology and teachers' capacity. For instance, the research of Kieu et al [31] revealed that teaching methods were one of the main reasons for student negative feedback toward ESD at the university level. Students claimed the courses were boring due to the lack of interactive teaching and learning, excessive content and poor facilities.…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
“…To promote ESD, the United Nations (UN) approved the Decade of Education for Sustainable Development (DESD) initiative, spanning from 2005 through to 2014 [2], and its follow-up initiative, the Global Action Programme (GAP) [3]. While ESD has had worldwide political support, the literature on ESD has mostly focused on case studies in developed nations; in other words, ESD has not yet been developed in Global South countries [4][5][6]. Indeed, in a review of 123 ESD-related articles selected from international peer-reviewed publications, Karatzoglou [7] showed that the majority (60.2%) of ESD articles come from Europe and the United State, while Asia and Africa account for only 8.9%.…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, SD concepts and issues were introduced in education in the 2000s, with the adoption of Vietnam Agenda 21 [14] and the National Action Plan on ESD in Vietnam 2010-2014 [15]. Principles of ESD have been favoured in Vietnam in certain ways (see [4][5][6]). For example, some SD themes have been promoted through integrating teaching at school and in extracurricular activities under a partnership between the Ministry of Education and Training (MOET) and other stakeholders, such as UNESCO (United Nations Educational, Scientific and Cultural Organization) and non-governmental organisations, since 2009, i.e., environmental education, saving energy, climate change education, education for disaster risk reduction, children's rights and HIV/AIDS [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…ESD, also known as sustainability literacy, provides individuals with the necessary knowledge, skills and motivation to successfully face contemporary challenges [30]. Of the ESD objectives mentioned by References [31,32] the following are relevant for the theme of this paper: to use a variety of teaching techniques that promote active (participatory), reflective, cooperative and experience-based learning, that can develop superior thinking skills; local relevance and cultural insertion of the methods being used; blending formal, non-formal and informal education, interdisciplinarity and the capacity to support labour force adaptability to the constant changes within organisations. ESD can be employed to achieve long-term cooperation habits, consistent knowledge sharing, creation of common or complementary skills, which are major factors in building and reinforcing sustainable digital ecosystems [33].…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%